Composting of Selected Organic Sludges Using Rotary Drum and Windrow System - Baharum, Zainal (2002)
Various organic sludges were composted by using rotary drum system and windrow system. In this research i.e. palm oil mill effluent (POME), food factory, sewage and leachate were composted with shredded wood and sawdust as bulking agents with a ratio of 3:1. The rotary drum used was modified from a 75Liter cement mixer with insulated drum. In composting of using windrow system, heap method was applied. In compo sting using rotary drum, fermentation process for sewage sludge, POME sludge, food factory sludge and leachate sludge took around 5, 5, 10 and 13 days respectively. The pH of the compost products was ranged from pH 6.0 to pH 8.0. The highest temperature was achieved around 60°C when heated air was supplied by heat gun. The moisture content profiles during compo sting was maintained around 50-70% moisture in the compost mass. The carbon content decreased and the nitrogen content increased towards the end of compo sting process, which resulted in the reduction of C/N ratio during compo sting process to below 20. The low C/N ratio of the final compost product was very important as the indicator of maturity. The compost substrates reduced around 50% based on wet weight basis at the end of the process. Overall, the composting for the whole process of organic sludges using rotary drum took around 30 to 35 days. Planting out test was performed with spinach, whereby the size of tree and colour of leaves were observed. The result showed that the best compost product was produced from sewage sludge compost. In compo sting using windrow system, two experiments were carried using 0.1% EM and 1.0% EM. The results observed from both experiments were almost similar. The difference was reflected in compost product from windrow system, which contained a higher number of total coliforms at around 10⁵- 10⁶ cfu/g because the temperature just increased to 37°C due to the small size of heap used. The whole compo sting process for windrow system only took around 30-35 days due to the high activity of EM during the compo sting process. The physicochemical and biological characteristics of these sludges were measured and can be applied in compo sting process. By using rotary drum and windrow system the products were improved based on nutrient contents and duration of compo sting process. Overall, the characteristics of the end products for both systems were similar and also complied with the United States Environmental Protection Agency (USEPA) standards.